Integrating Secondary and University Physics Education: An AI-Empowered Model for Cultivating Core Literacy - Liu, Jiao; Yu, Mingyu; Liang, Yuefeng; Huhemandula; Liu, Junfang (International Journal of Advanced AI Applications, 2025)
Addressing the prevalent issues of disconnection in physics education between secondary and higher education, the fragmented development of core competencies, and the homogenized teaching methodologies, this research employs the Outcome-Based Education (OBE) framework. It strategically merges the cultivation of core competencies with artificial intelligence (AI) technologies to develop a three-dimensional teaching reform model, structured around "Objective-Support-Implementation". This model specifically tackles the misalignment challenges in knowledge logic, competency requirements, and pedagogical methods between high school and university physics. It accomplishes this by establishing clear cross-academic-stage core competency goals, constructing a robust AI-assisted instructional support system, and implementing a reverse design teaching approach. Findings indicate that the proposed model can effectively integrate and enhance students' abilities in scientific reasoning, model construction, and experimental inquiry. This provides an operable and replicable teaching paradigm for cultivating top-tier talent in fundamental disciplines such as physics, offering a significant and innovative direction for future physics education reform.